2021
DOI: 10.3389/fgene.2020.601566
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Uncovers Novel Causative Variants and Additional Findings in Three Patients Affected by Glycogen Storage Disease Type VI and Fanconi−Bickel Syndrome

Abstract: Glycogen storage diseases (GSDs) are the heterogeneous group of disorders caused by mutations in at least 30 different genes. Different types of GSDs, especially liver GSDs, take overlapping symptoms and can be clinically indistinguishable. This survey evaluated the use of whole-exome sequencing (WES) for the genetic analysis of the liver GSD-suspected patients in three unrelated families. An in-house filtering pipeline was used to assess rare pathogenic variants in GSD-associated genes, autosomal recessive/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, a synergistic association with other biotechnologies, such as enzymatic assay for residual activity in FAODs, may allow a better characterization of new variants in order to define pathogenicity, customize follow-up and avoid overtreatment ( 116 ). Finally, the NGS approach allows genetic counseling for recurrence risk in further pregnancies ( 1 ), prenatal and preimplantation diagnosis ( 43 ).…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a synergistic association with other biotechnologies, such as enzymatic assay for residual activity in FAODs, may allow a better characterization of new variants in order to define pathogenicity, customize follow-up and avoid overtreatment ( 116 ). Finally, the NGS approach allows genetic counseling for recurrence risk in further pregnancies ( 1 ), prenatal and preimplantation diagnosis ( 43 ).…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
“…It is characterized by glycogen accumulation in liver and kidneys, with fasting hypoglycemia, hepatomegaly, tubular nephropathy (glucosuria, proteinuria, phosphaturia, bicarbonate wasting, and aminoaciduria), rickets, failure to thrive and short stature. The phenotypic variability ranges from mild presentation to diabetes mellitus ( 43 , 44 ). Patients are treated with hyperglucidic diet with low content of galactose.…”
Section: Iem Presenting With Hypoglycemia In Childhoodmentioning
confidence: 99%
“…The list has been revised twice: in 2017, the list was updated to include 59 genes (Kalia et al, 2017) and in 2021, 14 more genes were added to bring the total to 73 genes . Several papers have reported the identification of pathogenic/actionable PGx variants from WES/WGS datasets (Lee et al, 2016;Thauvin-Robinet et al, 2019;Eghbali et al, 2020). The 2017 ACMG guidelines indicated that PGx variants were being considered for inclusion in the future but none were considered for the 2021 guidance.…”
Section: Identification and Management Of Pgx Secondary Findingsmentioning
confidence: 99%
“…Other characteristics include shortness, rickets, poor growth, hepatomegaly, glucose, galactose intolerance, etc. ( 3 ) However, not all patients will develop typical clinical signs, including isolated glucosuria and hypokalemia ( 4 , 5 ). A high index of suspicion is needed for diagnosis due to its varied clinical presentations.…”
Section: Introductionmentioning
confidence: 99%